Criminal Punishment For Perpetrators of Group Fighting Criminal Acts - M. Fahmi Ardiansyah; M. Hidayat; Adies Kadir (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
The aim of the research is to determine the implementation of Article 170 paragraph (2) 1 of the Criminal Code concerning criminal acts involving joint forces committing violence against people resulting in injuries at the Surabaya District Court. The research method used is normative research, with a conceptual approach, namely legal research that looks for principles, doctrines and sources of law in a juridical philosophical sense. Result The judge's basis for consideration in handing down a decision against the perpetrator of the criminal act of group fighting based on the study of Decision Number: 411/Pid.B/2022/PN Sby is 5 (five), namely: (a). based on the prosecutor's indictment; (b). based on evidence at trial (both witness evidence, letters and the defendant's statement); (c). based on articles in the Criminal Code and Criminal Procedure Code; (d). based on legal facts revealed at trial; (e). based on the circumstances that led to the crime.